Perimortem dynamics of blood potassium concentration in patients dying in intensive care unit: A prospective nested cohort study - Schmidt, Matouš; Waldauf, Petr; Krbec, Martin; Duška, František (Journal of forensic sciences, 2022)
To enable diagnosis of hyperkalemia from the perimortem blood sample, we aim to describe the natural dynamics of blood potassium [K+ ] in patients dying after withdrawal of care while in an intensive care unit. In a nested sub-study of international Death Prediction and Physiology after Removal of Therapy (DePPaRT) project, we obtained serial whole-blood samples and analyzed ions and acid-base parameters in 23 patients just before life-sustaining treatment withdrawal, at the time of death, and after 5 and 30 min after death. Of the 631 patients in the DePPaRT study, we obtained consent and enrolled 23 subjects in the [K+ ] sub-study (12 M, 11F, aged 73 ± 14 years), mostly dying from irreversible brain damage or multi-organ failure. Blood [K+ ] rose from the median 4.3 (IQR 3.9; 4.8) mEq/L at treatment withdrawal to 5.2 (IQR 5.0; 6.8) mEq/L at death and then to 5.85 (IQR 5.2; 6.8) mEq/L after 30 min (mean rise of +0.64 mEq.L-1 .h-1 ). These changes were associated with progressive lactic and hypercapnic acidemia. After correcting the measured [K+] for pH by subtracting 0.6 mEq/L from [K+] for every 0.1 pH decrease from 7.40, the calculated [K+] remained normal or decreased from that measured at treatment withdrawal. In contrast to the late autolysis phase, the early changes of blood [K+ ] after death are slow and can be fully explained by progressive acidemia. Our data suggest that the diagnosis of hyperkalemia at death from a blood sample obtained within 30 min after death can be made by adjusting the [K+] concentration to a pH 7.40.
Keywords: draslík; postmortem chemistry; forensic pathology; hyperkalemia; lidé; Intensive Care Units; ionty; Prospective Studies; prospektivní studie; Ions; physiology of dying; hyperkalemie; Cohort Studies; kohortové studie; Potassium; Humans; dynamics of blood potassium; perimortem blood potassium; perimortem changes; jednotky intenzivní péče; Hyperkalemia